Glucose, starch, and dextrin utilization in the small intestine of steers - K.K. Kreikemeier; D.L. Harmon; T.B. Avery; Robert T. Brandt Jr. (Kansas Agricultural Experiment Station Research Reports, 1988)
Glucose infused into the abomasum of Holstein steers resulted in higher arterial glucose concentrations and increased net glucose absorption than either starch or dextrin infusions. Increasing infusion rates above 20 g/hr for both starch and dextrin resulted in no further increases in net glucose absorption. Even though the enzymatic starch and dextrin hydrolysis became saturated above 25 g/hr, the amount of starch and dextrin disappearing in the small intestine increased with higher infusion rates. This was accompanied by increased volatile fatty acid concentrations in the ileal fluid with starch and dextrin infusions, but not when glucose was infused. These data support two concepts: (l) microbial fermentation is involved in small-intestinal starch disappearance and (2) starch and dextrin hydrolysis in the small intestine of steers is more rate limiting than glucose absorptive capacity.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen' s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Glucose; Starch; Dextrin; Steers